Risk factors for heat related death during the August 2003 heat wave in Paris, France, in patients evaluated at the emergency department of the Hôpital Européen Georges Pompidou. Issue 7 (22nd June 2006) - Davido, A; Patzak, A; Dart, T; Sadier, M P; Méraud, P; Masmoudi, R; Sembach, N; Cao, T H
Abstract : Objectives: This study sought to determine the risk factors for short term mortality in the victims of the heat wave of August 2003 in France from among patients evaluated in our emergency department (ED). It was hypothesised that age, temperature, and some long term therapies and pre-existing pathologies were factors associated with short term mortality. Methods: A retrospective analysis of a seven day period. Four experts decided blindly, in pairs, whether a patient had presented with a heat related problem. Inclusion criteria were: core temperature ⩾38 °C and/or clinical signs of dehydration. Comparisons were made between the survivors and one month non-survivors for 57 different items. Short term mortality was defined as death in the ED or within the first month of the ED visit. Results: Of 841 patients attending the ED in the study period, 165 were included in the study, of which most were elderly women. Thirty one (18.8%) died within one month. Factors associated with short term mortality were: a greater degree of dependent living; more severe clinical condition on admission (higher temperature and heart rate, lower blood pressure, hypoxia, and altered mental status); higher values of blood glucose, troponin, and white blood cell count; lower values of serum protein and prothrombin levels; pre-existing ischaemic cardiomyopathy; pneumonia as associated infection; and previous psychotropic treatment. The total number of survivors at one year was 91. Conclusions: Although this study is limited because of the small sample size, the results have helped determine factors useful for future identification of patients at greatest risk of death in order to implement a more efficient patient care protocol.